Geometry and discrete mathematics : a selection of highlights - Fine, Benjamin, 1948-; Gaglione, Anthony M.; Moldenhauer, Anja (De Gruyter, 2018)
"This two-volume set collects and presents the fundamentals of mathematics in an exciting and pedagogically sound way. The present volume examines the most important basic results in geometry and discrete mathematics, along with their proofs, and also their history"- Resumé vydavatel
Keywords: geometrie; diskrétní matematika; geometry; discrete mathematics; elektronické knihy; učebnice; electronic books; textbooks